Anti-Markovnikov hydroarylation of alkenes via polysulfide anion photocatalysis - Li, Haoyu (2022)
A protocol for anti-Markovnikov hydroarylation of alkenes with aryl halides has been developed using polysulfide anions as photocatalysts in the presence of the Hantzsch ester and water under irradiation with visible light.